Analysis of Communication Satellite Utilization Indonesian Banking - Daffa Rizqi Prayudya; Firmansyah Firmansyah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
Space technology keeps innovating and giving us the benefit to make our life easier, including satellite banking. However, BRI become the first bank that own satellite and claims it could improve efficiency. Therefore, this research aims to look at the efficiency of selected banks in Indonesia and its productivity growth on efficiency by the satellite ownership. We also want to examine if the ownership of the satellite could impact bank efficiency. Methods that will be used are divided into two steps, which are DEA and Tobit regression. The result of this research shows us that bank BRI achieves the highest efficiency and productivity growth, compared with other selected banks. The ownership of satellites also has a positive significant impact on bank efficiency. It could be implied that owning satellite for banks is beneficial, policymakers should increase budget spending and other banks could own satellite.